Master or Servant? A Relief from the Kasta Hill Area and its Military Iconography - Kuzmin, Yuri (Anabasis. Studia Classica et Orientalia, 2016)
The results of the excavations of the “Macedonian” type tomb under the Kasta Hill near Amphipolis were presented at the 29th AEMTh conference (March 2016, Thessaloniki). Among the objects discussed in this presentation was a relief depicting a “warrior”. According to the archaeological team led by K. Peristeri, the relief was part of the decoration of the Kasta Hill monumental complex that functioned as a cenotaph or heroon of Hephaestion. A. Corso, a member of Peristeri’s team, suggested that this relief should be dated to the last quarter of the fourth century BC, and that it shows Alexander the Great at the head of Hephaestion’s funeral procession. However, the cavalry shield and helmet of the male figure indicate that the relief should be dated to a much later period. First, in the time of Alexander and at least in the early Diadochi period, the Macedonian cavalry did not use shields at all. The relief shows a round flat cavalry shield with a spina which started spreading across the Balkan region and the Hellenistic East not earlier than in the 270s BC. Second, the helmet in the relief (a variant of the κῶνος) shares many analogies in art and in artefacts from Macedonia, as well as other parts of the Hellenistic world, which do not date earlier than the end of the third century BC. Moreover, it is questionable whether in fact the relief under review was even part of the Kasta Hill complex, despite the location at which it was found. Quite possibly, it comes from a funeral monument of a Macedonian aristocrat who served in the cavalry and was a contemporary of the last Antigonid kings, Philip V (221–179 BC) or Perseus (179–168 BC). In the region of Kasta Hill and Amphipolis a few other “Macedonian” tombs have been discovered, and our relief might well have originated from a lost monument that once stood on a tumulus above one of them. The preserved fragment of the relief most probably does not represent the deceased, whose own representation appears to be lost, but a servant. Numerous parallels to such composition are found in votive and funerary monuments from Macedonia and abroad.